Bottle for Crixivan 400 mg HIV Protease Inhibitor - Science History Institute (2017)
Round plastic pill bottle labeled "Crixivan" 400 mg.
Keywords: HIV (Viruses)--Treatment; HIV infections--Treatment; Antiviral agents; Merck & Co.; Protease inhibitors; Medicine bottles; Drugs